2020
DOI: 10.1038/s41598-020-59195-w
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Amygdala Connectivity in Internet Addiction Disorder

Abstract: Recent studies have revealed structural and functional abnormalities in amygdala due to internet addiction (IA) associated with emotional disturbance. However, the role of amygdala connectivity that is responsible for emotion-cognition interactions is largely unknown in iA. this study aims to explore the amygdala connectivity abnormalities in iA. the functional and structural connectivity of bilateral amygdala were examined using seed-based connectivity analysis, and the structural integrity on white mater tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
2
14
0
1
Order By: Relevance
“…Our meta-analysis showed that there were brain regions associated with emotion regulation, such as the AMY. This finding is consistent with previous reports of AMY dysfunction in PIU ( 51 , 52 ), as well as with other addictions ( 53 , 54 ). The AMY is an important component of the basal ganglia and is involved in integrating and processing information about emotions and rewards ( 55 57 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our meta-analysis showed that there were brain regions associated with emotion regulation, such as the AMY. This finding is consistent with previous reports of AMY dysfunction in PIU ( 51 , 52 ), as well as with other addictions ( 53 , 54 ). The AMY is an important component of the basal ganglia and is involved in integrating and processing information about emotions and rewards ( 55 57 ).…”
Section: Discussionsupporting
confidence: 93%
“…fulfilling at least five of the DSM-5 IGD criteria or an IAT score >50 will define mechanistically meaningful study samples, whereas in fact the categorical IUD groups neither exhibit the same symptom constellation nor cover the whole symptom spectrum of IUD (Etkin, 2019). Several of the early studies employ sample sizes between 20 to 30, or often less than 20 per group (Cheng & Liu, 2020; Dong et al, 2010; Lorenz et al, 2013), which permits statistical detection power to be achieved but at the cost of sacrificing clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging evidence of aberrant habit system in IA was also revealed by neuropathology studies. A number of studies have found altered function of the PMC in IA (Cheng and Liu, 2020;Shin et al, 2020), which is a key region of the habit system accounting for the transformation of memory into a particular response sequence (Abe and Hanakawa, 2009). The cerebellum, traditionally considered a pure motor center, is now concerned for its various cognitive functions, including habit formation.…”
Section: Hyperactive Impulsive Habit Systemmentioning
confidence: 99%